Soothing the Inflamed Brain: Effect of Non-Steroidal Anti-Inflammatory Drugs on Alzheimer's Disease Pathology - J.M. Hoozemans, J.; Veerhuis, R.; M. Rozemuller, J.; Eikelenboom, P. (CNS & Neurological Disorders - Drug Targets, 2011)
Epidemiological studies suggest that systemic use of non-steroidal anti-inflammatory drugs (NSAIDs) can prevent or retard the development of Alzheimer's disease (AD). However, clinical trials investigating the effects of NSAIDs on AD progression have yielded mixed or inconclusive results. The aim of this review is to distinguish the role of inflammation and the molecular targets of NSAIDs in the different stages of AD pathology. AD brains are characterized by extracellular deposits of β-amyloid protein and intraneuronal accumulation of hyperphosphorylated tau protein. Already in the early stages of AD pathology β-amyloid protein deposits are associated with inflammatory proteins and microglia, the brain resident macrophages. Recently, two genome-wide association studies identified new genes that are associated with an increased risk of developing AD. These genes include CLU and CR1 which encode for clusterin and complement receptor 1 respectively. Both genes are involved in the regulation of inflammation. This strongly indicates that inflammation plays a central role in the aetiology of AD. In this review we will show that the primary targets of NSAIDs are involved in a pathological stage that precedes the clinical appearance of AD. The early, preclinical involvement of inflammation in AD explains why patients with clinical signs of AD do not benefit from anti-inflammatory treatment and suggests that NSAIDs, rather than having a direct therapeutic effect, may have preventive effects.
Keywords: Anti-inflammatory Prevention Trial (ADAPT)